Genetic inheritance of black seed coat in soybean. - CARPENTIERI-PIPOLO, V. (2021)
The standard phenotype of R gene is black hilum on black seed. The genetic control of several soybean (Glycine max L. Merr.) natural variants has not been studied. The genetic type T16 is the only occurrence with brown hilum on black seed coat. The aim of this chapter is to further a discussion the genetic control of seed black seed coat in soybean. The commercial cultivars Bragg, BR13 and BR6 present yellow seeds, their natural variants Bragg P and BR13P present black seed color and BR6M, LCV91-26 brown seed color. T16 was combined with these genotypes and it was found that the genetic control of the brown hilum trait in black seed coat of the T16 genotype was controlled by two loci segregating independently and controlling the expression of the color of the hilum and the seed coat color. The expression of the brown hilum trait in black seed coat is dependent on locus T_, which controls pubescence color; therefore it occurs only in genotypes with tawny brown pubescence (T_). Novel black soybean cultivars, breeding for specific characteristics, selected for direct use could, more suitable for human consumption will increase opportunities for exploring the global market of health and functional food industry and contribute as food source of both calorie and protein to combating hunger in undeveloped countries. Keywords: Seed coat color; Glycine max; black soybean.